Comercialização de produtos hortifrutícolas da agricultura familiar em Maringá : seus avanços e limites - Milagres, Paulo Roberto (2014)
This study aimed at describing and analyzing the process of organization of farmers in the context of association, regarding the marketing of products - mostly - from family farming in the region of Maringá, Paraná, Brazil, having as reference the Producer's Fair of Maringa. The survey was conducted through questionnaires and interviews. It describes how these farmer shave access to the public policies of marketing at the fair. In this research, the difficulties and obstacles faced by small producers to accessing these policies were identified, and the possible contribution soft his policy for the development of family farmers and their organizations were also described. Still, it explains the organizational process of the Producer's Fair of Maringá, as well as it identifies the conditional factors regulating the association and the associated producers, the possible strategies favorable to its development, and the most appropriate e means by which it could be strengthened. The study presented its characteristic sand importance in the economic and social context of the Producer's Fair of Maringá, and the efforts the state could make to create public policies that benefit family farmer sand their organizations. As a result of securing a marketplace for their products, and the subsequent increase in farmer's income, it could be concluded that the results were positive. This, in turn, also contributed to the development of additional supporting association entities and proved the cost/benefits to the local community because of the increase in the supply of fresh healthy food sat a reduced cost.